Analisis Korelasi Harga dan Mutu Kimiawi Kerupuk di Pasar Tradisional Cinde Palembang - Amri Winata; Kiki Yualiati; Siti Hanggita (Universitas Sriwijaya, 2015)
The objective of research was to determine the characteristics of the chemical quality of fish crackers and see the correlation between price and quality crackers from several price ranges. Research methods in this study using descriptive methods. The parameters observed in this research is chemical analysis include, water content, ash content, fat content, protein content, carbohydrate content and levels of Borax. Not found crackers containing borax. Based on the analysis of the correlation between the price of crackers with chemical quality is obtained that only ash content correlated with â€œrâ€ = 0.84.